2019
DOI: 10.1007/s40821-019-00122-z
|View full text |Cite
|
Sign up to set email alerts
|

What attracts multinational enterprises from the new EU member states to Poland?

Abstract: The main goal of this study is to examine empirically the determinants of multinational activity of firms from the new EU-12 member states in Poland during the period 1990-2014 using the negative binomial model. In particular, we test the predictions of competing theoretical models of the multinational enterprise to identify the investment motives for undertaking foreign direct investment in Poland. In addition to traditional country-pair characteristics such as absolute and relative market size and difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…In parallel with trade literature, many of the current FDI models present challenges with gravity estimations and suffer biases, which should be avoided. To do so, we extended earlier literature and applied for FDI gravity model practice recommendations from some influential new papers (Anderson, Larch, & Yotov, 2017, 2019Baier et al, 2019). Specifically, we used an estimation of the structural FDI gravity model, modified to account for the multilateral resistances with appropriate set fixed effects.…”
Section: B Review Of the Empirical Literature On Fdi Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel with trade literature, many of the current FDI models present challenges with gravity estimations and suffer biases, which should be avoided. To do so, we extended earlier literature and applied for FDI gravity model practice recommendations from some influential new papers (Anderson, Larch, & Yotov, 2017, 2019Baier et al, 2019). Specifically, we used an estimation of the structural FDI gravity model, modified to account for the multilateral resistances with appropriate set fixed effects.…”
Section: B Review Of the Empirical Literature On Fdi Determinantsmentioning
confidence: 99%
“…Initially, empirical studies for selected countries included a cross-country analysis and treated the entire region jointly (Brakman, 2008;Smarzynska & Wei, 2000). Later, some authors identified the main reasons for inward FDI flows to a single country or group of countries in the EU (Cieślik, 2017(Cieślik, , 2019Pirlogeanu, 2017). The most advanced recent study is the paper by Bruno et al (2017), in which the authors create a model for bilateral FDI flows of 35 OECD countries from 1985 to 2012 with pair-and time-fixed effects.…”
Section: B Review Of the Empirical Literature On Fdi Determinantsmentioning
confidence: 99%
“…The empirical studies for individual CEECs are more scarce. In particular, determinants of MNE activity in Poland were studied by Torrisi et al (2009) and more recently by Cieślik (2017Cieślik ( , 2019a.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, with the exception of the recent studies by Cieślik (2017Cieślik ( , 2019a, who used the number of firms with foreign capital participation as a proxy for the extent of MNE activity, the majority of previous studies made no attempts to test empirically the predictions derived directly from the NTMNE and differentiate between competing theoretical models. Hence, in contrast to the previous studies for Poland that used the number of firms with foreign capital participation as a dependent variable in this study, we use the actual data on the foreign direct investment position collected from the annual reports of the National Bank of Poland as a measure of inward FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical determinants of inward FDI into the whole group of Central and East European economies were studied by a number of authors including, inter alia, Lansbury, Pain, and Smidkova (1996) In particular, determinants of MNE activity in Poland were studied by Cieślik (1996Cieślik ( , 2006Cieślik ( , 2017Cieślik ( , 2019a, 2019b, 2019c) and Torrisi, Delaunay, Kocia, and Lubieniecka (2009). However, with the exception of the studies by Cieślik (1996Cieślik ( , 2006Cieślik ( , 2017Cieślik ( , 2019aCieślik ( , 2019bCieślik ( , 2019c, the previous studies made no attempts to test empirically the predictions derived directly from the NTMNE and discriminate between competing models. Moreover, the previous studies often used the number of firms with foreign capital participation as a dependent variable, while this study uses the actual data on the FDI position collected from the annual reports of the National Bank of Poland (NBP) as a measure of FDI.…”
Section: Literature Reviewmentioning
confidence: 99%